Warm-up intensity does not impact power sustainability in elite cyclists - Gnatiuk, E. A.; Myslicki, J.; Hittel, D. S.; Shearer, J. (Applied Physiology, Nutrition, and Metabolism, 2012)
Warm-up (WU) has consistently been shown to improve athletic performance. Active WUs are practiced at varying levels of exertion with the aim of maximizing performance. The objective of this study was to determine the impact of a WU performed at anaerobicthreshold (AnT), aerobic threshold (AeT), and a mixed-intensity WU (MIW) on performance in a power sustainability test (PST) at 98% of maximal aerobic power (MAP). Highly trained, competitive cyclists, category 3 or higher, participated in 4 separate visits (mean maximal oxygen consumption = 63.5 ± 4.6 mL/kg·min). Subjects were required to complete 3 PSTs, each preceded by a different WU protocol based on their AnT, AeT, and MAP. WUs varied in intensity but total work done (kJ) was kept constant. The 3 WU protocols, performed in random order, included (i) AnT, (ii) AeT, and (iii) MIW. The primary outcome measure of this study was total time to exhaustion (TTE) in seconds for each PST. Fingertip blood lactate (BLa) samples were taken and analyzed at 6 time points during each WU and subsequent PST. No significant differences in mean TTE were found between WUs at AnT (212.03 ± 14.06 s), AeT (216.3 ± 7.31 s), and MIW (228.6 ± 13.25 s) (p = 0.19). BLa concentration was significantly greater in the cyclists immediately following the AnT WU (5.7 ± 0.72 mmol·/L) compared with both the AeT WU (1.8 ± 0.29 mmol/L) and MIW (2.4 ± 0.35 mmol/L) (p < 0.001). This significant difference persisted in BLa samples taken 1 min prior to the PST in the AnT WU (3.2 ± 0.45 mmol/L) compared with the AeT WU (1.4 ± 0.21 mmol/L) and MIW (1.8 ± 0.26 mmol·/L) (p < 0.05). The differences in BLa concentration prior to each trial had no impact on performance. Varying responses to WU intensity suggest there is not one WU that will benefit all athletes equally; instead, WU is specific to the individual.